FAKTOR-FAKTOR YANG MEMPENGARUHI KEBUGARAN PERSONIL PKP-PK: GAYA HIDUP SEHAT DAN KEBIASAAN BEROLAHRAGA - Rizqillah, Zaki Abrian (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
This study aims to determine the level of strength and body fitness possessed by each ARFF personnel to support the preparedness and smoothness of tasks at each airport. The health and fitness of ARFF personnel are essential for the smoothness and success of an operation because the ARFF unit is a work unit at the airport that is required to have a prime and optimal physique to carry out the process of extinguishing fires and help all victims when an incident / accident occurs at the airport. This research uses a literature study research method. This article reviews the factors that influence the fitness of ARFF personnel, namely healthy lifestyles and exercise habits. The results of this literature review article are: 1) Healthy lifestyles affect the body fitness of ARFF personnel, and 2) exercise habits affect the body fitness of ARFF personnel.